Telehealth Consultation in the COVID-19 Era: Utilisation and Challenges of Virtual Platform - Khanom, Mehrunnissa; Chowdhury, Shahanara (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Abstract not available Chatt Maa Shi Hosp Med Coll J; Vol.19 (2); July 2020; Page 3-4